ETIOLOGY, PATHOGENESIS OF NECROBACTERIOSIS DIAGNOSTIC, PREVENTIVE AND TREATMENT METHODS - Djabbarova Dilnoza; Komilov Khajibay (Journal of new century innovations, 2023)
Annotation: The article presents information about the etiology,pathogenesis, distribution, pathogenetic characteristics of the pathogen Fusobacterum necrophorum, clinical symptoms,diagnostic methods, recommendations for treatment and prevention.